IDENTIFIKASI BAHAN PEWARNA DAN PENGAWET PADA SAOS TOMAT YANG BEREDAR DI KOTA JEMBER - Dyah Setyorini; Sonny Subiantoro; selviana selviana (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2010)
Tomato sauce is product of fresh tomato cultivation becoming tomato paste conducted through some processes. Tomato sauce distributed in Jember Regency uses additional food ingredients i.e colouring agent and preservative. The use of additional food ingredient has been ruled in the decree of Health Minister of Indonesia No. 722/Menkes/Per/IX/1988. According to the decree, the use of colouring agent and preservative may not exceed than 300 ppm, while for preservative i.e Natrium Benzoat may not be more than 1000 ppm. Since the excessive use of these materials may promote toxicity for the consumers. The data resulted were subsequently confronted to the Decree of Health Minister of Indonesia No. 722/Menkes/Per/IX/1988. The result showed that 30% of samples with colouring agent more than theits limit of use, and 30% with preservative more than its limit.Colouring agent degree of tomatoe sauce exceeding its limit i.e 300 ppm may allow it stored in body and cause liver disturbance. Histophatologically, degeneration of fat, pyknotic, hyperchromatism of nucleus and citolisis of plasma. The use of preservative more than its limit in tomatoe sauce i.e 1000 ppm may raise systemic effect such as urticaria, rhinitis, or anaphylactique shock. It was concluded that sample A brand showed that its colouring agent degree did not exceed its limitwhile its preservative did. While in sample B, C, D, E, F dan J, the degree of both colouring agent and preservative did not exceed their limit. Sample H showed that the degree of its colouring agent exceeded the limit of use while its preservative did not.